2017
DOI: 10.1177/1350650117699096
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis and tribological behaviors of three novel benzothiazole-derived borate esters as lubricant additives in mineral oil

Abstract: Three ashless and nonphosphorus benzothiazole-derived borate esters were synthesized by a halide-free green synthesis method. The results show that the hydrolytic stability and tribological characteristics have been significantly improved. Scanning electron microscopy was used to analyze the morphologies of the rubbing surfaces. X-ray absorption near edge structure spectroscopy was also adopted to investigate the thermal films and tribofilms of the synthesized additives. The analysis results indicate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, S and B were enriched in this region, which indicates that compounds CuS and B-containing compounds may be generated during the friction process (Xiong et al , 2016). CuS and B-containing compounds can produce excellent anti-wear and anti-friction effects (Tang et al , 2017). When lubricated by CU-KL, there were obvious furrows in the worn area, as well as shedding pits on the local zone [Figure 8(c)].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, S and B were enriched in this region, which indicates that compounds CuS and B-containing compounds may be generated during the friction process (Xiong et al , 2016). CuS and B-containing compounds can produce excellent anti-wear and anti-friction effects (Tang et al , 2017). When lubricated by CU-KL, there were obvious furrows in the worn area, as well as shedding pits on the local zone [Figure 8(c)].…”
Section: Resultsmentioning
confidence: 99%
“…It is not only widely used with a large amount of reliable data. So, the anti-wear agent in rapeseed oil was chosen as the focus of the research, and 14–45 data on additives were obtained from the literature. A total of 79 additives were classified into six categories: borate esters (Group 1), triazine derivatives (Group 2), thiazoles (Group 3), formate esters (Group 4), phosphoric acid (Group 5), and thiophenes (Group 6).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that nitrogencontaining heterocyclic compounds, which have dense chemical structures and good thermal stability, are capable of forming an adsorption film on the surface of the friction pair and are increasing the strength of the film, making them potential green lubricant additives [11]. There have been extensive studies of the tribological properties of N-containing heterocyclic compounds, such as triazine and its derivatives [12][13][14], benzotriazole [15][16][17], benzoxazole [17], benzimidazole [17,18] and benzothiazole derivatives [19,20]. It has been found that these nitrogenous compounds have excellent extreme pressure, anti-wear, friction-reduction properties, and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, benzothiazole can be used as an ashfree, multifunctional, green, and environmentally friendly lubricating oil (or grease) additive [20]. Benzothiazole contains a continuous closed conjugate system containing ten p-electrons that are hybridized by sp 2 , in which the S atom provides a pair of p-electrons which are more likely to coordinate with metal ions to form an adsorption film [22].…”
Section: Introductionmentioning
confidence: 99%